2015
DOI: 10.5114/ceji.2015.50840
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Pro-inflammatory cytokines for evaluation of inflammatory status in endometriosis

Abstract: The aim of the studyThe aim of the study was to investigate the serum pro-inflammatory cytokine profile in patients with diagnosed endometriosis.Material and methodsThe study included 160 women, who were divided in two study groups (Group I – endometriosis; Group 2 – healthy). We evaluated the serum levels of interleukin (IL)-1β, IL-5, IL-6, IL-7, and IL-12, and of tumour necrosis factor α (TNF-α) with the use of Human Multiplex Cytokine Panels.ResultsThe serum level of IL-1β, IL-6, and TNF-α is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 40 publications
6
56
2
5
Order By: Relevance
“…) Gazvani, Bates, and Vince (2001). andMalutan, Drugan, and Costin (2015) found no differences in IL-12 levels at various stages of the disease, different phases of the menstrual cycle, or with respect to clinical complaints of dysmenorrhea, infertility, or chronic pelvic pain.…”
mentioning
confidence: 87%
“…) Gazvani, Bates, and Vince (2001). andMalutan, Drugan, and Costin (2015) found no differences in IL-12 levels at various stages of the disease, different phases of the menstrual cycle, or with respect to clinical complaints of dysmenorrhea, infertility, or chronic pelvic pain.…”
mentioning
confidence: 87%
“…The increased serum levels of the same markers TNF‐α are a cytokine with powerful inflammatory, cytotoxic, and angiogenic effects that has a key role in the initiation of the cascade of numerous inflammatory cytokines and other inflammatory factors. In addition, TNF‐α has been shown to play a pivotal role in the pathology of endometriosis . In our study, TNF‐α was investigated both in serum and in peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effectivity of alpha-lipoic acid in the treatment of endometriosis, which is an antioxidant and anti-inflammatory drug that has never been experimented in the treatment of endometriosis. In previous studies, increased oxidative stress parameters have been found both in ectopic endometrial tissues and in peripheral blood samples in endometriosis [26][27][28]. Oxidative stress is one of the factors in the pathophysiology of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia and PPARγ deletion induce inflammatory injuries in ECs, while endometriosis presents with high level of pro-inflammatory cytokines for stimulating ECs (2729). Accordingly, hypoxia, endometriosis, PPARγ deletion were classified into inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%